2020
DOI: 10.1093/jxb/eraa096
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP53–IAA4 module inhibits adventitious root development in Populus

Abstract: Adventitious roots (ARs) are important for some plants that depend on clonal propagation. In this study, we demonstrate that a salt-responsive gene module is involved in the negative regulation of AR development in poplar. In this module, the expression of bZIP53 is induced by salt stress and it encodes a transcription factor with transactivation activity. Overexpression or induced expression of bZIP53 in poplar lines resulted in inhibition of AR growth, while heterologous overexpression of bZIP53 in Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…In arabidopsis hypocotyls it has been shown that ARF7 act together with ARF19 as positive AR regulators by activating the downstream transcription factors ORGAN BOUNDARIES DOMAIN ( LBD ) LBD16 and LBD18 ( Lee et al, 2019 ). Recently, Zhang et al (2020) showed that the overexpression of the poplar bZIP53 transcription factor had a negative effect on AR development by controlling the expression of IAA4-1 and IAA4-2 ( Figure 1 ). bZIP53 was shown to bind to the promoter of IAA4-1 and IAA4-2 and activate their expression.…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 99%
“…In arabidopsis hypocotyls it has been shown that ARF7 act together with ARF19 as positive AR regulators by activating the downstream transcription factors ORGAN BOUNDARIES DOMAIN ( LBD ) LBD16 and LBD18 ( Lee et al, 2019 ). Recently, Zhang et al (2020) showed that the overexpression of the poplar bZIP53 transcription factor had a negative effect on AR development by controlling the expression of IAA4-1 and IAA4-2 ( Figure 1 ). bZIP53 was shown to bind to the promoter of IAA4-1 and IAA4-2 and activate their expression.…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 99%
“…For example, poplar PtabZIP1L is mainly expressed in roots and can mediate the development of lateral roots and drought resistance by regulating various metabolic pathways [ 12 ]. Poplar bZIP53 is inducible in gene expression by salt stress and negatively regulates the development of adventitious roots [ 13 ]. The poplar AREB1 can regulate drought responses and tolerance of Populus trichocarpa by affecting histone acetylation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the up-regulated genes, EAT-UpTF identified LATERAL ORGAN BOUNDARIES DOMAIN 19 (LBD19), LBD18 and LBD16 as upstream regulators, which are involved in auxin-dependent lateral root emergence ( Feng et al, 2012 ) ( Table 3 ). Meanwhile, BASIC REGION/LEUCINE ZIPPER MOTIF 53 (bZIP53) and bZIP11, which negatively regulate adventitious root formation and primary root growth in an auxin-dependent pathway ( Weiste et al, 2017 ; Zhang et al, 2020 ), were retrieved as overrepresented upstream TFs for the IAA-repressed genes ( Table 4 ). Overall, the EAT-UpTF analysis reliably identified upstream TFs for a group of GOIs.…”
Section: Resultsmentioning
confidence: 99%